PENGARUH PEMBERIAN LIMBAH SERASAH JAGUNG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt - Ester Juni Ernita; Husna Yetti2; Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The researchaimed to examinethe effect of waste litter cornand obtain the best to the growthand yield ofsweet corn(Zea mayssaccharataSturt). This study has been conducted in Jl.kartama, RT. 04 RW. 07 subdistrict Marpoyan Damai, Pekanbaru from November 2016 to Februari 2017. The researchexperiment use complete design random (CDR) consisting of 4 treatment and 5 replicationthen obtained20 experimentunits. The treatment tested was giving is :K0 = without waste litter corn, K1 = 10 ton/ha (6 kg/plot) of waste litter corn, K2 = 20 ton/ha (6 kg/plot) of waste litter corn, K3 = 30 ton/ha (6 kg/plot) of waste litter corn, K4 = 40 ton/ha (6 kg/plot) of wastelitter corn. The observed used is plant height,male flowersappear,female flowersappear,harvestingage, the production per plot, weight per seed of husk, diameter corncob without husk,cob lenght, and the number of seed lines. Waste litter of corndosage of 24 kg / plot is the best treatment on plant height parameters, male flowersappear, the number of seed lines, and production per plot. Corn waste litter dosage at 18 kg / plot is the best treatment on the parameters of female flowersappear, harvesting age, weight per seed of husk, cob length, and the diameter corncob. Keywords : Waste litter corn, Sweet corn